Analyzing the Relation Between Exchange Rate and Remittances Inflow Using VECM : Empirical Evidence from India - Prakash, Sanjana; Yadav, Ekta; Mujoo, Rachna (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : The study focused on analyzing the dynamic relationship between remittances and the exchange rate. Remittances have played a vital role in fostering economic growth and stability, particularly in developing economies. By providing a stable source of capital, remittances support household consumption, investment, and poverty reduction, thereby stimulating demand and improving living standards. Additionally, remittances enhance human capital development, contributing to overall economic stability and growth. Methodology : This paper used the vector error correction model and investigated the intricate relationship between remittances inflows and other macroeconomic variables. This study shed light on the dynamic nature of the exchange rate and the multifaceted impact, which was seen in the case of remittances inflow in India. Data for the study ranged from the year 1990 – 2023 and were extracted from the Reserve Bank of India. The study further suggested that effective measures should be taken to minimize the exchange rate volatility to mitigate its negative impacts on the remittances inflow. Findings : The findings suggested a paradoxical relationship between remittances and the exchange rate. Given the volatile behavior of the exchange rate, its impact on the remittances received was dynamic. Practical Implications : The study provided a relevant base for policymakers to critically examine the role of the exchange rate during the policy formulation stage. It also supplemented the findings of various studies by taking up the lesser discussed aspects. Originality : This study is original and novel in that its findings highlighted both the apparent and underlying relationships between remittances and the exchange rate.